2014
DOI: 10.1017/s1751731114001505
|View full text |Cite
|
Sign up to set email alerts
|

The use of banquettes of Posidonia oceanica as a source of fiber and minerals in ruminant nutrition. An observational study

Abstract: In the search for new food sources that contribute to the optimization of livestock production this paper discusses the possibility of using waste (called banquettes) of a marine plant commonly found on the Mediterranean coasts: Posidonia oceanica. The idea stems from the use of a waste that in summertime generates large costs because it is considered bothersome on the beaches. Thus, tons and tons of residues are collected each year from the beach, being destined for incineration. However, alternative uses for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 10 publications
(7 reference statements)
4
16
0
Order By: Relevance
“…Based on our previous results on the chemical composition of P. oceanica , the aim of the present study was to assess the effects of introducing P. oceanica as a substitute for straw in the feed of dairy goats on milk production and metabolism (blood metabolites, including oxidative stress).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous results on the chemical composition of P. oceanica , the aim of the present study was to assess the effects of introducing P. oceanica as a substitute for straw in the feed of dairy goats on milk production and metabolism (blood metabolites, including oxidative stress).…”
Section: Introductionmentioning
confidence: 99%
“…With an annual yield of 35 million litres (some individuals have reached a mean milk production of about 1.3 kg day −1 over 305 days of lactation), the milk of Murciano-Granadina goats is characterised by a fat content of 5.4 g, a protein content of 3.6 g and a dry extract content of 14.5 g per 100 g and is considered highly suited for the production of different varieties of cheeses. 5 Based on our previous results on the chemical composition of P. oceanica, 3 the aim of the present study was to assess the effects of introducing P. oceanica as a substitute for straw in the feed of dairy goats on milk production and metabolism (blood metabolites, including oxidative stress).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical and nutrient properties of P. oceanica showed that this marine plant contains more ash and lignin fraction (ADL) than other traditional forage sources such as cereal straw or rye grass hay. Before starting the analysis of the different applied treatments and as we pointed out in the results section, we should discard the PO‐60% group.…”
Section: Discussionmentioning
confidence: 99%
“…The collection and management of the dried marine plant residues that were used as feedstuff was fully described in a previous report, as well as the chemical analysis of the product . Briefly, after permission for sampling from the local government, samples of banquettes of P. oceanica from six different points of the selected area were randomly collected on the same day directly from the beach above the water line, washed in a warehouse with distilled water and sun dried for 48 h. Approximately 500 g of each sample of plant material was chopped and two subsamples of 200 g each were placed in airtight plastic containers and sent to the laboratory for mineral and chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation